SAFEGUARDING INTANGIBLE CULTURAL HERITAGE IN CHINA: POLICY EVOLUTION AND CHALLENGES (Journal of Creative Industry and Sustainable Culture, 2024)
Safeguarding intangible cultural heritage is a comprehensive systematic project, with governmental policy regulation and guidance constituting essential components. China has been exploring policies for safeguarding ICH for over a century. However, true legislative protection began in the late 1990s, drawing on international practices and summarizing continuous exploration since the late Qing Dynasty and the early Republican Government. This paper reviews China's policy frameworks for ICH protection, providing insights for achieving similar goals under varying national contexts while also highlighting several challenges in the implementation of these policies. Keywords: Opinions on Further Strengthening the Protection of Intangible Cultural Heritage, Intangible Cultural Heritage, Policy.